Fabrication of Graphene Nanoplatelet/Epoxy Nanocomposites for Lightweight and High‐Strength Structural Applications. (3rd April 2018) - Kim, Joonhui; Cha, Jaemin; Jun, Gwang Hoon; Yoo, Sung Chan; Ryu, Seongwoo; Hong, Soon Hyung
Abstract: Graphene nanoplatelets (GNPs), the most important mass‐produced graphene, are fabricated as a mechanical reinforcement for epoxy matrix nanocomposites. Current performance of GNPs as a reinforcing filler is limited by their agglomeration and weak interfacial interaction with certain polymer matrices. Herein, an approach to produce noncovalently functionalized GNPs (F‐GNPs) is reported that can be extended to the industrial level of mass production. The one‐step functionalization process uses melamine, a low‐cost chemical, to improve the interfacial adhesion and dispersion in an epoxy matrix. The mechanical properties of nanocomposites prepared with the F‐GNP flakes are much better (94.3% and 35.3% enhancements in Young's modulus and tensile strength, respectively) than those of the unfilled pure epoxy. Experimental data are analyzed using the Halpin–Tsai model. The fabrication process developed in this paper provides a strategy to use GNPs at the industrial level in lightweight and high‐strength structural applications. Abstract : Through strategy of noncovalent functionalization by melamine, a graphene nanoplatelet (F‐GNP)/epoxy nanocomposite is developed for usage at the industrial level in lightweight and high‐strength structural applications. The incorporation of melamine drives excellent mechanical properties of the nanocomposite via homogeneous dispersion and enhanced interfacial adhesion between GNP flakes and epoxy matrix.